Adaptive and innate immune pathogenesis of bullous pemphigoid: A review - Yan, Tianmeng; Zhang, Zhenying (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune blistering disease that primarily affects elderly individuals. The presentation of BP is heterogeneous, typically manifesting microscopic subepidermal separation with mixed inflammatory infiltrate. The mechanism of pemphigoid development is unclear. B cells play a major role in pathogenic-antibody production, and T cells, type II inflammatory cytokines, eosinophils, mast cells, neutrophils, and keratinocytes are also implicated in the pathogenesis of BP. Here, we review the roles and crosstalk of innate and adaptive immune cells in BP.